(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
This article is concerned with the cultural context within which Adam Smith’s ideas were forged, namely the theological disputes originated in the Presbyterian Church during the Scottish Enlightenment. These events influenced Smith’s perceptions of human nature as well as his understanding of the underpinnings of everyday human interaction. They also determined Smith’s views on the nascent commercial society and led to his belief in the beneficial effects of individual economic initiatives subject to the influence of the market mechanism. Therefore, one is entitled to say that the foundations of economic thinking were born within natural theology.